De-escalation of Children's Vulnerability to Sexual Violence in the School Environment of Madrasah Aliyah 40 Persatuan Islam Pamulihan Village - Happy Yulia; Irpan Maulana; Tyara Oktavianti; Yusi Siti Pertiwi; Ahmad Bahrudin Doni Boro (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
The incidence of sexual violence against teenagers in schools truly shakes the heart of every moral person. Thus, inclusive and informative sexual education should be an integral part of the school curriculum, which helps children understand their rights and gives them the tools to protect themselves. This service uses a socialization strategy by conducting counseling to students of Madrasah Aliyah 40 Persatuan Islam Sarongge. In this sexual violence counseling, the speaker presented the theme